Increased Consumption of Unsaturated Fatty Acids Improves Body Composition in a Hypercholesterolemic Chinese Population - Haldar, Sumanto; Ponnalagu, Shalini; Osman, Farhana; Tay, Shia Lyn; Wong, Long Hui; Jiang, Yuan Rong; Leow, Melvin Khee Shing; Henry, Christiani Jeyakumar (Frontiers in Nutrition, 2022)
While an increase in fat intake and the resulting excess calorie intake are implicated in weight gain, different fat types exert variable effects on body composition, with unsaturated fats showing favorable effects on body composition in Western population. Whether and to what extent these associations apply to Asian population have not been established. We investigated the effects of two separate Asian-based oil blends, rich in unsaturated fats, made from refined rice bran, sesame, and flaxseed oils, in comparison with refined olive oil, on body composition using dual-energy X-ray absorptiometry (DXA), from an 8-week, parallel design, randomized trial in 66 men (58.7 ± 5.71 years old, 23.0 ± 2.38 kg/m2) and 69 postmenopausal women (59.1 ± 5.34 years old, 21.7 ± 2.52 kg/m2), with borderline hypercholesterolemia. Despite increases in mean daily intakes of total energy (approximately +400 kcal/day, female, and approximately +240 kcal/day, male), as well as increases in percentage of calories from fats and proteins and decreases in percentage of calories from carbohydrates during the dietary intervention period, there were no significant changes in total body fat mass in both genders and also in all treatment groups. While total body weight increased slightly (0.36 ± 0.12 kg, p = 0.005) in women during intervention, this was mainly due to gain in lean mass (0.38 ± 0.081 kg, p < 0.0001). Correspondingly, there were reductions in total body fat (%), android fat (%), and gynoid fat (%) in women. No significant differences between the 3 intervention oil types were found in any of the measured parameters in either gender. Increasing relative intakes of unsaturated fats may prevent fat mass gain and circumvent muscle mass loss associated with menopause in older Asian women. Long-term studies are needed to confirm findings. This study had been registered on clinicaltrials.gov (Identifier No.: NCT03964857, https://www.clinicaltrials.gov/ct2/show/NCT03964857).